PENGARUH ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED TERHADAP NILAI PERUSAHAAN PADA (PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2014-2018) - Mikrad, Mikrad; Syukur, Abdul (Universitas Muhammadiyah Tangerang, 2019)
The purpose of this study is to assess the extent to which the capital structure and profit of a company affect the value of a company and increase the prosperity of shareholders with a non-behavioral observation method of secondary data types entitled the influence of Economic Value Added and Market Value Added to the value of the company in the food and beverage sub sector registered on the Indonesia Stock Exchange in 2014-2018. For hypothesis testing using the F test, t test and coefficient of determination. T test is used to test hypotheses simultaneously, F test is used to test hypotheses partially, while the coefficient of determination is used to test how much the role of independent variables (EVA) and (MVA) together explain the changes that occur in the dependent variable (Company Value ). The analysis used is using multiple linear regression conducted through the program Eviews 9.0. Keywords: Economic Value Added, Market Value Added, and company value